Potential of Inflammatory Biomarkers as Diagnostic Tools for Paediatric Inflammatory Multisystemic Syndrome related to SARS-CoV-2: Literature Review - Nia Maylani Hutagaol; Ivan Santiago (Science Midwifery, 2022)
The World Health Organization has named the enveloped RNA virus Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Clinical aspects and pathogenic mechanisms between hyperinflammatory disease and SARS-CoV-2 are triggering factor for the out brake of autoinflammation disease and autoimmune dysregulation. This condition is known as Paediatric Inflammatory Multisystem Syndrome Temporally (PIMS-TS) related to SARS-CoV-2 or Multisystem Inflammatory Syndrome in Children (MIS-C) related to COVID-19. There are similarities between MIS-C and other diseases, that is overlapping clinical manifestations that lead to delaying diagnosis. Therefore, whether inflammatory biomarkers could be used to distinguish between these conditions are needed to be investigated. In orderd to distinguish MIS-C from infection and other inflammatory condition, it will continue to be a challenge as the COVID-19 pandemic. Therefore, a study is needed to investigate whether inflammatory biomarkers could be used to distinguish between these conditions.